# Lim X → 7 4 − √ 9 + X 1 − √ 8 − X - Mathematics

$\lim_{x \to 7} \frac{4 - \sqrt{9 + x}}{1 - \sqrt{8 - x}}$

#### Solution

$\lim_{x \to 7} \left[ \frac{4 - \sqrt{9 + x}}{1 - \sqrt{8 - x}} \right]$ It is of the form $\frac{0}{0}$

Rationalising the numerator and the denominator:

$\lim_{x \to 7} \left[ \frac{\left( 4 - \sqrt{9 + x} \right)}{1} \times \frac{\left( 4 + \sqrt{9 + x} \right)}{\left( 4 + \sqrt{9 + x} \right)} \times \frac{1}{\left( 1 - \sqrt{8 - x} \right)} \times \frac{\left( 1 + \sqrt{8 - x} \right)}{\left( 1 + \sqrt{8 - x} \right)} \right]$

=  $\lim_{x \to 7} \left[ \frac{16 - \left( 9 + x \right)}{\left( 4 + \sqrt{9 + x} \right)} \times \frac{\left( 1 + \sqrt{8 - x} \right)}{1 - \left( 8 - x \right)} \right]$

=  $\lim_{x \to 7} \left[ \frac{- 1\left( - 7 + x \right)\left( 1 + \sqrt{8 - x} \right)}{\left( 4 + \sqrt{9 + x} \right)\left( - 7 + x \right)} \right]$

=  $\lim_{x \to 7} \left[ \frac{- \left( 1 + \sqrt{8 - x} \right)}{4 + \sqrt{9 + x}} \right]$

= $- \left( \frac{1 + \sqrt{8 - 7}}{4 + \sqrt{9 + 7}} \right)$

=  $\frac{- 2}{4 + 4}$

=  $\frac{- 1}{4}$

Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 29 Limits
Exercise 29.4 | Q 15 | Page 28